Phylogenetic position and taxonomy of the enigmatic Orobanche krylowii (Orobanchaceae), a predominatly Asian species newly found in Albania (SE Europe) - Frajman, Božo; Carlón, Luis; Kosachev, Petr; Sánchez Pedraja, Óscar; Schneeweiss, Gerald M.; Schönswetter, Peter (Phytotaxa, 2013)
We report on the occurrence of Orobanche krylowii in the Alpet Shqiptare (Prokletije, Albanian Alps) mountain range in northern Albania (Balkan Peninsula). The species was previously known only from eastern-most Europe (Volga-Kama River in Russia), more than 2500 km away, and from adjacent Siberia and Central Asia. We used morphological evidence as well as nuclear ribosomal ITS sequences to show that the Albanian population indeed belongs to O. krylowii and that its closest relative is the European O. lycoctoni, but not O. elatior as assumed in the past. Both Orobanche krylowii and O. lycoctoni parasitize Ranunculaceae (Thalictrum spp. and Aconitum lycoctonum, respectively). We provide an identification key and a taxonomic treatment for O. krylowii, and suggest the IUCN category CE (critically endangered) for the highly disjunct Albanian population.